Ireland : 2010 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2010)
Irish policymakers have gained significant credibility, through assertive steps, to deal with the most potent sources of vulnerability. A continuation of vigorous policy efforts is required with an emphasis on risk management. Much progress has been made on the financial stability agenda, but a special bank resolution scheme is required. The government has stayed on course, toward their consolidation goals. A medium-term fiscal framework incorporating expenditure ceilings is a valuable management tool that will help create greater transparency of fiscal priorities and reduce fiscal volatility.